Formation and mosaicity of coccolith segment calcite of the marine algae Emiliania huxleyi. Issue 1 (22nd November 2017) - Yin, Xiaofei; Ziegler, Andreas; Kelm, Klemens; Hoffmann, Ramona; Watermeyer, Philipp; Alexa, Patrick; Villinger, Clarissa; Rupp, Ulrich; Schlüter, Lothar; Reusch, Thorsten B. H.; Griesshaber, Erika; Walther, Paul; et al.
Abstract : Coccolithophores belong to the most abundant calcium carbonate mineralizing organisms. Coccolithophore biomineralization is a complex and highly regulated process, resulting in a product that strongly differs in its intricate morphology from the abiogenically produced mineral equivalent. Moreover, unlike extracellularly formed biological carbonate hard tissues, coccolith calcite is neither a hybrid composite, nor is it distinguished by a hierarchical microstructure. This is remarkable as the key to optimizing crystalline biomaterials for mechanical strength and toughness lies in the composite nature of the biological hard tissue and the utilization of specific microstructures. To obtain insight into the pathway of biomineralization of Emiliania huxleyi coccoliths, we examine intracrystalline nanostructural features of the coccolith calcite in combination with cell ultrastructural observations related to the formation of the calcite in the coccolith vesicle within the cell. With TEM diffraction and annular dark‐field imaging, we prove the presence of planar imperfections in the calcite crystals such as planar mosaic block boundaries. As only minor misorientations occur, we attribute them to dislocation networks creating small‐angle boundaries. Intracrystalline occluded biopolymers are not observed. Hence, in E. huxleyi calcite mosaicity is not caused by occluded biopolymers, as it is the case in extracellularly formed hard tissues of marine invertebrates, but by planar defects and dislocations which are typical for crystals formed by classical ion‐by‐ion growth mechanisms. Using cryo‐preparation techniques for SEM and TEM, we found that the membrane of the coccolith vesicle and the outer membrane of the nuclear envelope are in tight proximity, with a well‐controlled constant gap of ~4 nm between them. We describe this conspicuous connection as a not yet described interorganelle junction, the "nuclear envelope junction". The narrow gap of this junction likely facilitates transport of Ca 2+ ions from the nuclear envelope to the coccolith vesicle. On the basis of our observations, we propose that formation of the coccolith utilizes the nuclear envelope–endoplasmic reticulum Ca 2+ ‐store of the cell for the transport of Ca 2+ ions from the external medium to the coccolith vesicle and that E. huxleyi calcite forms by ion‐by‐ion growth rather than by a nanoparticle accretion mechanism.